A meta-analysis: Effect of androgens on reproduction in sows - Guo, Zhenhua; Lv, Lei; Liu, Di; Ma, Hong; Radovic, Cedomir (Frontiers in Endocrinology, 2023)
The mechanisms by which male hormones affect the development of ovaries and follicles has been studied by injecting exogenous androgens into sows. This may provide a reference for human polycystic ovary syndrome (PCOS), and can also provide guidance for improving the litter size of sows. We present a meta-analysis of studies published in the past 30 years on the effect of androgens on the ovulation rate of sows. A total of 517 papers were analyzed. The results showed that both testosterone (T) and dihydrotestosterone (DHT) injected into sows were positively related to the ovulation rate. T did not have a relevant effect on swine in vivo blastocyst survival rate. DHT had a negative phase with respect to blastocyst survival rate. Pig T-androgen receiver affinity was higher than the analogous affinity for DHT; this is different in humans. This suggests that sows are not suitable as human PCOS experimental animal models. To improve the litter size of sows, future research should focus on the mixed use of T and DHT, and the timing of use should be consistent with the periodic changes in androgen levels in sows. In addition, the welfare of experimental sows should be considered with reference to the clinical symptoms of PCOS.